Exploring the clinical features and complications of type 1 diabetes mellitus in Saudi Arabia: A retrospective analysis - Ayman Abdullah Al Hayek; Asirvatham Alwin Robert; Abdullah Alshablan; Asma M. Almutairi; Elaf Ibrahim Alanzi; Faisal Alarjan; Halimah Ahmed Althurwi; Kholod Alamri; Nada Almshhen; Nuha Althibait; Nawaf Mugren Bin Mugren; Rawan Alyahya; et al. (Journal of Family Medicine and Primary Care)
Background and Aim: On a global scale Type 1 diabetes (T1D) ranks high on the list of most prevalent endocrine metabolic disorders; it affects children and adolescents. Frequently, T1D causes complications that can be serious, acute and chronic. This present study aims to investigate the clinical features and complications associated with T1D in Saudi Arabia. Methods: In this retrospective cohort study, individuals with T1D were investigated at the Diabetes Treatment Center, Prince Sultan Military Medical City (PSMMC) in Riyadh, Saudi Arabia, focusing on patients aged 14 to 60 years. Data were collected on each patient, regarding demographic information (gender, age) and diabetes-related criteria (duration of diabetes, age when diagnosed, current and initial HbA1c values, and treatment modalities). Accurate documentation was done of the disease-related complications such as hypertension, dyslipidemia, and a plethora of diabetic retinopathy (whether non-proliferative, proliferative, or macular edema), plus nephropathy/end-stage renal disease, neuropathy, coronary artery disease, peripheral vascular disease, and cerebrovascular disease. Results: The patient cohort comprises 46.1% males and 53.9% females. Different groups revealed similar biochemical markers, like HbA1c and creatinine clearance. Patients with diabetes for a longer duration had a higher probability of statin intake (P = 0.0001) and GLP-1 therapy (P = 0.004). A striking rise was evident in microalbuminuria and retinopathy, some disease-related complications, with the duration of diabetes. While a few of the complications show higher frequency in patients having HbA1c >7.5%, several differences are noted, although not statistically significant; this is indicative of the complexities in the relationships between diabetes management and the final results. Conclusion: In summary, younger patients with a more contracted timespan of diabetes will experience fewer complications than those with a lengthier duration of the disease, who in reality will face higher risks. Therefore, to achieve improved health outcomes, diabetes patients require effective treatment management.